Prevention of travel-related infections in solid organ and hematopoietic cell transplant recipients - Rita Wilson Dib; José Henao-Cordero; Joseph Sassine; Emily A. Siegrist; Nelson Iván Agudelo Higuita (Therapeutic Advances in Infectious Disease)
The growing population of transplant survivors receiving a solid organ transplantation (SOT) or a hematopoietic cell transplantation (HCT) and the emergence of cellular therapies are contributing to an increase in high-risk travelers to different regions of the world. Timely pretravel evaluations are essential for risk stratification and a segway to planning proper immunization, personalized antimicrobial prophylaxis, and preventative counseling based on individual medical conditions, immune status, and potential drug-drug interactions. In addition, clinicians can provide emergency and specialized medical center contacts as available. We herein review the available strategies for the prevention and management of travel-related infections in adult recipients of HCT and SOT.